Virtual currency and reputation-based cooperation incentives in user-centric networks - Bogliolo, A.; Polidori, P.; Aldini, A.; Moreira, W.; Mendes, P.; Yildiz, M.; Ballester, C.; Seigneur, J.-M. (8th IEEE International Wireless Communications and Mobile Computing Conference, 2012)
Cooperation incentives are essential in user-centric networks to motivate users to share services and resources (including bandwidth, computational power, and storage space) and to avoid selfish nodes to hinder the functioning of the entire system. Virtual currency and reputation mechanisms are commonly adopted in online communities to boost participation, but their joint application has not been deeply explored, especially in the context of wireless communities, where not only the services, but even the enabling infrastructure is opportunistically built by community members. This paper investigates the combined use of virtual currency and reputation-based incentives in the specific context of a community of users with Wi-Fi enabled devices capable of establishing ad-hoc connections.